EFFECT OF MUTAGENS ON SEED GERMINATION, PLANT SURVIVAL AND QUANTITATIVE CHARACTERS OF HORSEGRAM (Macrotyloma uniflorum (LAM.) VERDC) : Life Science-Botany - SADASHIV N, BOLBHAT; VIKRAM D, BHOGE; KONDDIRAM N., DHUMAL (International Journal of Life Science and Pharma Research, 2012)
Seeds of horsegram (Macrotyloma uniflorum (Lam.) Verdc) cv. Dapoli Kulthi-1 and cv. Rajapur-5 were treated with various doses/ concentrations of gamma radiation (100 to 400Gy), EMS (0.2 to 0.5%) and their combinations. The physiological effects on seed germination (7 days) and plant survival at 45 days after sowing were investigated. Gradual reduction in seed germination and plant survival was recorded with increase in dose / concentration of mutagens. Lower doses of gamma rays 100Gy (89.3%), EMS 0.2% (86.2%) and in combination 100Gy + 0.2% (85.6%) showed highest germination percentage in cv. Dapoli Kulthi- 1. In cv. Rajapur- 5 highest germination percentage was recorded in 100Gy (87.3%), EMS- 0.2% (85.2%) and in combination 200Gy + 0.2%EMS (82.17%). The survival percent in both cultivars of horsegram was decreased as the dose of gamma radiation increased. Significant reduction in survival percentage was observed at the higher doses (400Gy) of gamma radiation, EMS (0.5%) and in their combination (400 + 0.5%EMS).Various micromutations with respect to quantitative characters were scored in M1 population. For both cultivars almost all the mutagenic treatments (except very few) caused decrease in plant height, primary branches per plant, days required for first flowering, number of pods per plant, pod length, number of seeds per pod and seed yield per plant during M1.